Selectivity and morphological engineering of a unique gallium−organic framework for antibiotics exclusion in water - Mahdi Barati; Heidar Raissi; Afsaneh Ghahari (npj Clean Water)
Abstract Antibiotic pollutants from pharmaceutical waste pose a severe threat to ecosystems. This study explores the use of gallium-metal organic frameworks (Ga-MOFs) and imide-functionalized MOFs (F-MOFs) for antibiotic removal through adsorption. Using molecular dynamics simulations, we evaluated the adsorption of amikacin (AMC), kanamycin (KMC), and tobramycin (TMC) on MOF and F-MOF surfaces. The simulation results suggest that these adsorbents could be effective in adsorbing a significant portion of these antibiotics. π-π stacking interactions contributed to strong binding between antibiotics and substrates. Additionally, metadynamics simulations revealed free energy minima of –254.29 KJ/mol for KMC/MOFs and –187.62 KJ/mol for KMC/F-MOFs, confirming complex stability. This theoretical approach highlights the potential of Ga-MOF-based materials in mitigating antibiotic pollution’s environmental and health impacts.